Effect of fractional urea clearance on survival of hemodialysis patients in relation to gender - Ferreira, Juliana Cunha [UNESP]; Andrade, Luís Gustavo Modelli de [UNESP]; Barretti, Pasqual [UNESP]; Caramori, Jaqueline Costa Teixeira [UNESP]; Balbi, André Luis [UNESP]; Martin, Luis Cuadrado [UNESP] (Taylor & Francis Inc, 2008)
Many studies have demonstrated the relationship between dialysis dose and survival. Global mortality is similar among men and women; however, the influence of dialysis dose in the survival could be more intensive between women. Therefore, we conduct an observational study to evaluate the gender-related impact of single pool Kt/V (spKt/V) on the survival of patients submitted to hemodialysis in a university hospital. We found that survival was lower in groups with spKt/V smaller than 1.2 than in those with Kt/V between 1.2 and 1.4. Among female patients, spKt/V smaller than 1.2 had a more adverse effect in survival than among men with a comparable Kt/V. Otherwise, among women, the dialysis dose had an impact in survival even with Kt/V greater than 1.4. Thus, fractional urea clearance more heavily influenced the survival of females than males in hemodialysis patients.
Keywords: fractional urea clearance; survival; hemodialysis adequacy; gender